Transitivity
In this post we prove various transitivity laws.
$(a \wedge b) \wedge (b \wedge c) \quad \Rightarrow \quad (a \wedge c)$
\[\begin{align} &(a \wedge b) \wedge (b \wedge c) && \\ &= (a \wedge c) \wedge (b \wedge b) &&\text{Associativity and Commutativity} \\ &\Rightarrow (a \wedge c) &&\text{Specialization} \end{align}\]$(a \Rightarrow b) \wedge (b \Rightarrow c) \quad \Rightarrow \quad (a \Rightarrow c)$
\[\begin{align} &(a \Rightarrow b) \wedge (b \Rightarrow c) && \\ &= (\overline{a} \vee b) \wedge (\overline{b} \vee c) &&\text{Material Implication} \\ &= (\overline{a} \wedge \overline{b}) \vee (\overline{a} \wedge c) \vee (b \wedge \overline{b}) \vee (b \wedge c) &&\text{Distributivity and Associativity} \\ &= (\overline{a} \wedge \overline{b}) \vee (\overline{a} \wedge c) \vee \color{red}F \vee (b \wedge c) &&\text{Noncontradiction} \\ &= (\overline{a} \wedge \overline{b}) \vee (\overline{a} \wedge c) \vee (b \wedge c) &&\text{Identity} \\ &= (\overline{a} \wedge \overline{b}) \vee (\overline{a} \wedge c) \vee (b \wedge (c \wedge (c \vee \overline{b}))) &&\text{Absportion} \\ &= (\overline{a} \wedge \overline{b}) \vee (\overline{a} \wedge c) \vee ((b \wedge c) \wedge (\overline{b} \vee c)) &&\text{Associativity and Commutativity} \\ &= (\overline{a} \wedge (\overline{b} \vee c)) \vee ((b \wedge c) \wedge (\overline{b} \vee c)) &&\text{Distributivity} \\ &= (\overline{a} \vee (b \wedge c)) \wedge (\overline{b} \vee c) &&\text{Distributivity} \\ &= (\overline{a} \vee b) \wedge (\overline{a} \vee c) \wedge (\overline{b} \vee c) &&\text{Distributivity and Associativity} \\ &\Rightarrow (\overline{a} \vee c) &&\text{Specialization} \\ &= (a \Rightarrow c) &&\text{Material Implication} \\ \end{align}\]$(a = b) \wedge (b = c) \quad \Rightarrow \quad (a = c)$
\[\begin{align} &(a = b) \wedge (b = c) && \\ &= ((a \Rightarrow b) \wedge (a \Leftarrow b)) \wedge ((b \Rightarrow c) \wedge (b \Leftarrow c)) &&\text{Double Implication} \\ &= ((a \Rightarrow b) \wedge (b \Rightarrow a)) \wedge ((b \Rightarrow c) \wedge (c \Rightarrow b)) &&\text{Mirror 2 times} \\ &= ((a \Rightarrow b) \wedge (b \Rightarrow c)) \wedge ((c \Rightarrow b) \wedge (b \Rightarrow a)) &&\text{Associativity and Commutativity of} \ \wedge \\ &= (a \Rightarrow c) \wedge (c \Rightarrow a) &&\text{Transitivity of } \ \Rightarrow \\ &= (a \Rightarrow c) \wedge (a \Leftarrow c) &&\text{Mirror} \\ &= (a = c) &&\text{Double Implication} \\ \end{align}\]$(a \Rightarrow b) \wedge (b = c) \quad \Rightarrow \quad (a \Rightarrow c)$
\[\begin{align} &(a \Rightarrow b) \wedge (b = c) && \\ &= (a \Rightarrow b) \wedge ((b \Rightarrow c) \wedge (b \Leftarrow c)) &&\text{Double Implication} \\ &= (a \Rightarrow b) \wedge ((b \Rightarrow c) \wedge (c \Rightarrow b)) &&\text{Mirror} \\ &= ((a \Rightarrow b) \wedge (b \Rightarrow c)) \wedge (c \Rightarrow b) &&\text{Associativity} \\ &\Rightarrow (a \Rightarrow c) \wedge (c \Rightarrow b) &&\text{Transitivity of } \ \Rightarrow \\ &\Rightarrow (a \Rightarrow c) &&\text{Specialization} \end{align}\]$(a = b) \wedge (b \Rightarrow c) \quad \Rightarrow \quad (a \Rightarrow c)$
\[\begin{align} &(a = b) \wedge (b \Rightarrow c) && \\ &= ((a \Rightarrow b) \wedge (a \Leftarrow b)) \wedge (b \Rightarrow c) &&\text{Double Implication} \\ &= ((a \Rightarrow b) \wedge (b \Rightarrow a)) \wedge (b \Rightarrow c) &&\text{Mirror} \\ &= (b \Rightarrow a) \wedge ((a \Rightarrow b) \wedge (b \Rightarrow c)) &&\text{Commutativity and Associativity} \\ &\Rightarrow (b \Rightarrow a) \wedge (a \Rightarrow c) &&\text{Transitivity of } \ \Rightarrow \\ &\Rightarrow (a \Rightarrow c) &&\text{Specialization} \end{align}\]